1977
DOI: 10.1139/b77-280
|View full text |Cite
|
Sign up to set email alerts
|

Unusual plasties in an endomycorrhizal root

Abstract: Unusual plastids, identified as globular chromoplasts directly developed from proplastids, observed in the infected root cells of Ornithogalum umbellatum L. are tentatively interpreted as an expression of host reaction to fungus infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

1979
1979
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 4 publications
1
15
0
1
Order By: Relevance
“…In mycorrhizal tobacco, mycorradicin (data not shown) and cyclohexenone (Maier et al 2000) have been observed. This mycorrhiza-induced accumulation of apocarotenoids, as well as the ultrastructural observations of Scannerini and Bonfante-Fasolo (1977) and Dexheimer et al (1988), possibly indicates that the role of plastids during the development of arbuscular mycorrhizas might not be restricted to basic metabolic pathways like fatty acid biosynthesis, nitrogen assimilation or starch deposition.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In mycorrhizal tobacco, mycorradicin (data not shown) and cyclohexenone (Maier et al 2000) have been observed. This mycorrhiza-induced accumulation of apocarotenoids, as well as the ultrastructural observations of Scannerini and Bonfante-Fasolo (1977) and Dexheimer et al (1988), possibly indicates that the role of plastids during the development of arbuscular mycorrhizas might not be restricted to basic metabolic pathways like fatty acid biosynthesis, nitrogen assimilation or starch deposition.…”
Section: Discussionmentioning
confidence: 56%
“…Because of several ultrastructural features, most notably the existence of a tubular network within the plastid stroma, Dexheimer et al (1990) speculated about the secretion of terpenoids as part of a plant defense reaction to the fungal colonization. Scannerini and Bonfante-Fasolo (1977) had already described large plastids containing lipophilic vesicles close to fungal arbuscules in mycorrhizal roots from Ornithogalum umbellatum L.. These plastids eventually lysed and released their vesicular contents into the cytoplasm; they were interpreted as chromoplasts due to the yellowish colour of the roots.…”
Section: Discussionmentioning
confidence: 99%
“…The AM‐induced activation of the plastid‐located MEP pathway may be related to these observations and to earlier reports on unusual plastids in mycorrhizal roots, which resemble chromoplasts and always occur close to fungal arbuscules ( Dexheimer et al . 1990 ; Scannerini & Bonfante‐Fasolo 1977). DXS and DXR transcript accumulation might be a marker for such a transition in root plastid development to parallel chromoplast formation for carotenoid biosynthesis specifically involved in AM physiology.…”
Section: Discussionmentioning
confidence: 99%
“…Phillips & Hayman (1970), , Ashford et al (1975), and Ebel et al (1958) have used sectioning and cytochemical techniques to reveal further details of endophyte morphology and to localise inorganic compounds associated with mycorrhizal infection. In addition, Scannerini & Bonfante-Fasolo (1977) and Kinden & Brown (1975 a, b) have used electron microscopy techniques, including thin sectioning and staining and scanning electron stereoscopy, to reveal much about fungal morphology and host-endophyte interaction. *The term "infection" is not used in this paper in the pathology sense to infer a disease condition.…”
Section: Introductionmentioning
confidence: 99%